Formulation and Evaluation of Gastro Retentive Floating Tablets of Simvastatin using Hydrophilic Rate Retardant (Bangladesh Pharmaceutical Journal, 2012)
Gastro retentive floating tablet of Simvastatin was prepared by direct compression technique using Methocel K4M as the rate controlling polymer. The hydrophilic cellulose derivative, Methocel K4M was evaluated for its gel forming and release controlling properties. Sodium bicarbonate and citric acid were incorporated as gas generating agents. The effects of soluble components (sodium bicarbonate and citric acid) and gel forming agents on drug release profile and floating properties were investigated. The tablets from all formulations were evaluated for thickness, diameter, weight variation, hardness, and friability. The tablets were also tested for the buoyancy studies and in vitro drug release studies. The drug release study was evaluated for eight hours using USP XXII paddle-type dissolution apparatus using 0.1N HCl with 1% Sodium Lauryl Sulphate as dissolution medium. The release mechanisms were explored and explained with zero order, first order, Higuchi, Hixon Crowell and Korsmeyer equations. The release rate, extent and mechanisms were found to be governed by the polymer content. It was found that the mean dissolution time, percentage drug release, release rate constant and diffusion exponent were influenced significantly by the amount of polymer incorporation. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12575 Bangladesh Pharmaceutical Journal 15(2): 119-126, 2012